Employee Performance through Learning & Innovation in Mediating Organizational Structure and Knowledge Oriented Leadership - Ramdani Bayu Putra; Havidz Aima; Yulasmi Yulasmi (Dinamika Pendidikan, 2022)
Employee performance is one important factor that is useful in helping the organization. This relates to the achievement of the objectives contained in the vision and mission of an organization. This study aimed to analyze the performance of employees with an organizational structure and knowledge-oriented leadership based on learning innovation and organizational suitability. The population of this research was the employees of the Regional Secretariat of the City of Padang, totaling 222 people. The sampling technique used the Census method, where the entire existing population was used as a research sample. While the data analysis technique used Structure Equation Modeling (SEM) with hypothesis testing using SmartPLS 3. The results of the research hypothesis showed that knowledge-oriented organizational structure and leadership had a significant effect on learning innovation as well as employee performance. Empirical facts found that learning innovation had a significant effect on employee performance. Meanwhile, knowledge-oriented leadership had no significant effect on employee performance. Furthermore, learning innovation proved to have a significant effect in mediating organizational structure and knowledge-oriented leadership on employee performance. The contribution of this research, to be able to improve the performance of employees, organizational leaders can provide training and education as well as distribute knowledge and skills in supporting the work of employees.